2005
DOI: 10.1080/14733140500330146
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders from parent to child: Mothers’ perceptions of transgenerational effect

Abstract: Primary prevention focuses on the reduction of risk factors. Children of mothers with an eating disorder are a proven “at risk” group, because children internalise their experiences. Prevention in the field of eating disorders has as yet only addressed children of seven or eight upwards and only in school‐based programs which did not incorporate mothers. This project targeted mothers with an eating disorder who had children under the age of thirteen. The hypothesis is that if these mothers can be encouraged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
0
13
0
2
Order By: Relevance
“…As mães mostraram muitas dificuldades em comprar e preparar os alimentos. Com a participação nos grupos, puderam refletir sobre as condutas que estavam tomando na educação dos filhos e reavaliaram as mensagens ambivalentes que lhes transmitiam acerca da alimentação 32,33 . A generalização de tais achados, contudo, deve ser realizada com cautela, pois ambos os estudos contaram com número reduzido de participantes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As mães mostraram muitas dificuldades em comprar e preparar os alimentos. Com a participação nos grupos, puderam refletir sobre as condutas que estavam tomando na educação dos filhos e reavaliaram as mensagens ambivalentes que lhes transmitiam acerca da alimentação 32,33 . A generalização de tais achados, contudo, deve ser realizada com cautela, pois ambos os estudos contaram com número reduzido de participantes.…”
Section: Discussionunclassified
“…Ainda assim, somente um estudo apresentava uma proposta interventiva de prevenção de transmissão de comportamentos alimentares inadequados 32 . Os demais artigos apenas apontaram a necessidade de cuidados preventivos [19][20][21]26,28,29,31,34 , principalmente nas escolas (coibindo as práticas de bullying, por exemplo) e dentro do grupo familiar, mas a literatura científica encontrada ainda não acompanha tal demanda.…”
Section: Discussionunclassified
“…Especially in cases of early neglect or abuse: the problem is not simply the low levels of oxytocin (Heim et al, 2009), but also the decreased oxytocin responses to social support (Macdonald & Macdonald, 2010). If remained un-corrected, the unfavorable attachment styles and oxytocin patterns can be transferred to the next generation (Barnett, Buckroyd, & Windle, 2005;Brethelton & Munholland, 1999;Champagne, 2008;Ward et al, 2001). The aim of the correction is to restore the balance between the defense system (activated as a result of threat and uncertainty) and the attachment system (built on the experiences of proximity, trust, and care in a social context).…”
Section: Discussionmentioning
confidence: 99%
“…However, a Norwegian study that followed up an initially childless sample of women (N = 1.206) found that those who became a mother during the study experienced a decrease in their ED problems compared to those who remained childless and concluded that motherhood may have a positive effect on ED (von Soest & Wickstrøm, 2008). Nevertheless, Barnett et al (2005) hold that a trans-generational effect from parent to child may be a result of maternal ED, which makes the children an at risk group. They concluded that the development of treatment groups for mothers with ED may reduce the damage to both mother and child.…”
Section: Introductionmentioning
confidence: 94%